Wideband Bidirectional Circularly Polarized S-Slot Antenna with Dielectric Superstrate - Bancha Luadang; Pisit Janpangngern; Chuwong Phongcharoenpanich (My University, 2024)
This paper presents the design of a circularly polarized (CP) wideband S-slot antenna with a bidirectional radiation pattern, using a dielectric superstrate (DS) to increase the gain. The antenna achieves an enhance axial ratio (AR) bandwidth and reduced back lobe of radiation pattern. The S-slot antenna is positioned midway between a rectangular dielectric superstrate and an S-slot radiating element, which has a dielectric constant of εr = 4.3. The DS acts as a lens, refracting the electric field to combine the antenna beam and increase the antenna gain. For performance evaluation, the S-slot radiating element without the DS was compared to the proposed antenna. The antenna size is optimized for a center frequency of 5.5 GHz. The square DS contributes significantly to the bandwidth ratio, achieving an axial ratio AR ≤ 3 dB across the design frequency range (|S11| ≤ -10 dB) of 4.0–6.25 GHz. This antenna design is suitable for wireless communications and 5G sub-6 GHz applications, such as in long bridge/tunnel areas, coal mines communications, radio frequency identification (RFID) systems, and various wireless communication systems.
Keywords: Antenna Design and Analysis; Advanced Antenna and Metasurface Technologies; Microwave Engineering and Waveguides